2022
DOI: 10.1002/oby.23659
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic characterization of the maternal prenatal gastrointestinal microbiome by pregravid BMI

Abstract: Objective: The incidence of women entering into pregnancy with BMI indicating overweight or obesity is rising with concurrent increases in adverse complications such as gestational diabetes. Although several studies have examined the compositional changes to the microbiome across BMI classifications, there has been no investigation regarding changes in microbial function during pregnancy.Methods: A total of 105 gastrointestinal microbiome biospecimens were used in this analysis. Biospecimens were sequenced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Cadmium and polycyclic aromatic hydrocarbons were used as examples for biotransformations that had implications for both the pregnancy and the offspring. Driesbach, et al [22] using retrospective, cross-sectional metagenomic analysis found that maternal microbiome composition in the late second trimester was an effective predictor of birth weight. Maternal microbiome composition at 36 weeks of pregnancy was also shown to be a good predictor of immune cell composition in the newborn at birth.…”
Section: Crafting and Managing The Next Generationmentioning
confidence: 99%
See 2 more Smart Citations
“…Cadmium and polycyclic aromatic hydrocarbons were used as examples for biotransformations that had implications for both the pregnancy and the offspring. Driesbach, et al [22] using retrospective, cross-sectional metagenomic analysis found that maternal microbiome composition in the late second trimester was an effective predictor of birth weight. Maternal microbiome composition at 36 weeks of pregnancy was also shown to be a good predictor of immune cell composition in the newborn at birth.…”
Section: Crafting and Managing The Next Generationmentioning
confidence: 99%
“…For example, serotonin and dopamine levels and/or signaling are controlled by specific gut bacteria [49][50][51]. In addition, the important role of a balanced gut microbiome in fear extinction helps to protect against anxiety, depression, and mental illness [33] Table 1 illustrates the areas where our body's microbiota intercedes to affect our life and even our body's immediate afterlife [22,29,33,42, (Table 1).…”
Section: American Journal Of Biomedical Science and Researchmentioning
confidence: 99%
See 1 more Smart Citation